Glycosyl flavonoids from Salvia sclareoides: contribution to the development of a new functional food - Abraços, L. (2019)
Salvia sclareoides is a plant of spontaneous Portuguese vegetation that has relevant properties, as part of its cholinergic action and in the prevention of the formation of amyloid plaques. Previous studies suggested [1,2] that this species of Salvia can be used as a functional food and also in the development of a food supplement in the context of the prevention and treatment of Alzheimer's disease. Sweet cookies were developed with different concentrations (2 % and 5 %) of S. sclareoides, previously ground for particle size reduction (2.00 mm). The nutritional composition was determined, namely: moisture content, ash, total protein, total fat, dietary fibre and salt [3]. The available carbohydrates and the energy value were obtained by calculation. Extracts were prepared from the dried aerial parts of the plant. Different extraction methodologies were used and the phenolic profile of each extract was determined by high performance liquid chromatography with diode array detection. The antioxidant and anticholinesterase activities of these extracts were also evaluated. The ethanol extract of S. sclareoides, with 2.00 mm grain size, presented the highest concentration of phenolic compounds (143.74 mg GAE/g dry extract) and antioxidant activity (68.45 %), while the aqueous extract showed the best anticholinesterase activity (30.86 %). The glycosylated flavonoids rutin and (7-O-glucosyl)luteolin are clearly the major constituents present in all extracts, along with epicatechin, ellagic acid and (7-O-glucosyl)naringenin.